Effectiveness of the Legislative Body DPRK of Bireuen District in Preparing the Draft Qanun - Hasyem, Muhammad; Muklir, Muklir; Maryam, Maryam; Syamsuddin, Syamsuddin (Program Magister Administrasi Publik, 2024)
This study aims to analyze the effectiveness of the performance of members of the Legislative Body of the Bireuen Regency People's Representative Council (DPRK) in completing Regional Regulations (Qanun). The study was conducted at the Bireuen DPRK Office using a descriptive qualitative approach, which aims to provide an in-depth picture of the problems faced in the legislative process. The results of the study indicate that the effectiveness of the performance of members of the Bireuen DPRK Legislative Body is influenced by several factors, including limited human resources (HR), incompatibility of worker characteristics, and obstacles in communication with related agencies, such as the Ministry of Law and Human Rights. Interviews with various informants such as the Legislative Body Coordinator, Secretary, and Bireuen Regency Secretariat revealed that the lack of competent HR and delays in the Qanun ratification process were the main obstacles in achieving the target of completing the Qanun. In addition, the important role of communication between legislative members and the central government also influenced the effectiveness of completing the Qanun. This study suggests the need to increase HR capacity through training and recruitment of new, more competent members so that the legislative process can be more effective and in accordance with the targets that have been set.